Reducing Bandar-Lurus Flow-Velocity To Minimize Erosion of Batang-Kurao Riverbank, Padang - Februarman, Februarman; Mera, Mas; Ginawa, Dega (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2025)
The Bandar-Lurus River empties into the Batang-Kurao River at an almost perpendicular confluence. As a result, when the Bandar Lurus flowed the 2021-August-18 flood-discharge, for example, the Kurao river-bank collapsed. If this is allowed to last longer, then the resident houses near the river bank could be damaged. The flow velocity is predicted using the Manning formula, and the resistance coefficients are averaged using the Einstein-Banks formula. Both formulas are then solved using the Newton-Raphson method on the MS Excel platform. The objective of this study is to slow down the Bandar downstream velocity of the as slowly as possible to minimize damage to the Kurao river-bank. The first step is to lower the longitudinal slope of the Bandar bed from 0.0012 to 0.0007. As a result, the downstream velocity is expected to slow down from 1.85 to 1.68 m/s, and the water level is also estimated to drop from 6.79 to 5.98 m. The next step is to replace the Bandar-bed material from the ground with irregular sharp-rock fragments. Consequently, the velocity is expected to slow down from 1.68 to 1.19 m/s, but the water level is estimated to rise from 5.98 to 6.94 m. This is the Bandar velocity that can be engineered considering that the channel-top elevation in the downstream is only 8.24 m including the freeboard.